The Association of Tau With Mitochondrial Dysfunction in Alzheimer's Disease - Cheng, Ying; Bai, Feng (Frontiers in Neuroscience, 2018)
Increasing evidence suggests that abnormally hyperphosphorylated tau plays a vital role in the pathogenesis of Alzheimer’s disease (AD). Mitochondrial dysfunction also has a recognized role in the pathophysiology of AD. In recent years, mitochondrial dysfunction has been strongly associated with tau pathology in AD. Overexpression of hyperphosphorylated and aggregated tau appears to damage the axonal transport, leading to abnormal mitochondria distribution. In addition, pathological tau impairs mitochondrial dynamics by regulating mitochondrial fission/fusion proteins, and further causes mitochondrial dysfunction and neuronal damage. Moreover, mitochondrial dysfunction is also involved in promoting tau pathology in AD. In this article, we evaluate the relationship between phosphorylated tau and mitochondrial dysfunction in AD.